PERANCANGAN BALOK BAJA KOMPOSIT GEDUNG KOPERASI DI POLITEKNIK NEGERI BANDUNG - iim, husnul khotimah (Universitas Majalengka, 2021)
The Cooperative Building Design at the State Polytechnic of Bandung uses ETABS with composite steel construction. The earthquake analysis method used based on SNI-03-1726-2012 article 7.7.2 is static equivalent because the building is classified as category II and the height does not exceed three floors. Based on the value of SDS = 0.87 and SD1 = 0.777 with the results of type D, it is in accordance with article 7.2.2 earthquake force bearer frame system that is allowed to use a special moment bearer frame. The ratio capacity of the main beam obtained is 0.81. Keywords: composite, cooperative building, equivalent static, special moment bearer frame